CONSTRUCTION OF BLOCK DESIGNS WITH NESTED ROWS AND COLUMNS - Rasul, L.; Iqbal, I. (Journal of Research (Science), 2007)
In row-column design the experimental units are grouped in two directions. These blocking may represented a further blocking factor or provide replications of the basic experimental designs. Incomplete block designs with nested rows and columns are designs for v treatments in s block of size k = pq < v. We describe a general method of constructing such designs using a set of cyclic shifts. This method is used to construct efficient designs. The majority of the designs given is new and extended previously published designs.